The variability and causes of organic carbon retention ability of different agricultural straw types returned to soil. Issue 5 (4th March 2017) - Wang, Han; Wang, Lei; Zhang, Yannan; Hu, Yu; Wu, Jihua; Fu, Xiaohua; Le, Yiquan
ABSTRACT: Retaining the organic carbon (C) content of agricultural straw when returned to soil is restricted by rapid decomposition. In order to clarify the difference in returned straw decomposition and the causes, and to develop a straw returning mode with high-efficiency of organic C accumulation, the decomposition processes of corn, soybean, rice and wheat straws were systematically studied in fields. When returned in situ (the original planting area), the C in soybean straw was decomposed most quickly with a decomposition constant of 0.00542 d –1, but wheat straw showed a longer retention in soil with 0.00303 d –1 . However, for ex situ return of all straw in one area away from in situ return, soybean straw was decomposed most slowly (0.00452 d –1 ) and wheat straw more quickly (0.00652 d –1 ). The sequence of C decomposition rate in 270 d was soybean > corn > rice > wheat ( in situ ) and corn > wheat > rice > soybean ( ex situ ). Both surrounding soil and straw nature were important factors influencing the decomposition rate. The farmland with rice and wheat rotation retained more C from returned straws due to its high moisture and low nitrogen (N) content, while the soybean field was a contrast. Soybean straw had a low decomposition rate after ex situ return due to its low N content and high C/N ratio. The farmland of wheat–rice rotation combined with soybean straw ex situ return may develop into a field of higher C retention ability.